x^3+12x^2+13x=x solve for x

First simplify: x^3 + 12x ^2 + 13x -x = 0

x^3 + 12x^2 + 12x =0

Take out x as a common factor x (x^2 + 6x + 6) =0

One solution is x=0

To get the other apply quadratic formula with a = 1 b = 6 and c =6 to get

[-6 +/- Sqr (6 ^2 - 4 *1 * 6)]/ 2*1

[-6 + Sqr (12)]/2 or [-6 - Sqr (12)]/2

which simplifies to -3 + Sqr 3 and -3 -Sqr3

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up